Legal Protection for Creditors after the Implementation of the Auction of Mortgage Rights whose Selling Value has not been Paid Off the Debtor's Remaining Debt - Rahman, Yanti BT. (Jurnal Konstatering, 2022)
This study aims to determine and analyze the Legal Protection of the feasibility value of credit guarantees made after the Auction Decision No. 136/75/2019 dated 03 May 2019 at PT. Bank Mandiri Raha Branch, and to find out and analyze legal remedies that can be taken by creditors to obtain repayment of the remaining post-auction debt on collateral objects of Tangunggan Rights. The research approach method used in this thesis is a sociological juridical legal research method. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the BW Civil Code (Burgelijk Wetboek); Act No. 4 of 1996; Act No. 10 of 1998 Act No. 37 of 2004; Regulation of the Minister of Finance Number 213/PMK.06/2020 concerning Guidelines for Auction Implementation, as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is analysis. The results of the study show that the legal protection of the eligibility value of credit guarantees, namely the creditor must still pay attention to the appropriate value for the mortgage object according to market prices. The legal remedy that can be taken by creditors to obtain post-auction settlement of the remaining debt on the mortgage object is by filing a bankruptcy petition at the Commercial Court.Keywords: Agreements; Credit; Execution; Mortgage.